PENGELOLAAN TINGKAT PEMAKAIAN LAPANGAN PENUMPUKAN DAN TINGKAT PENGGUNAAN DERMAGA di PT TERMINAL TELUK LAMONG - Yugowati Praharsi (Jurnal Teknologi Maritim, 2019)
Judgement Yard Occupancy Ratio (YOR) and Berth Occupancy Ratio (BOR) at PT Terminal Teluk Lamong have not entered the optimal operational performance. YOR and BOR into one assessment in looking at the performance of the port of unloading so that relevant to researched. The purpose of this study is to: 1. Analyze the relationship between YOR and BOR in the PT Terminal Teluk Lamong, 2. Make mathematical modeling, 3. Compile estimates the development performance upcoming of YOR and BOR using a linear regression, forecasting double moving average, and double exponential smoothing with the smallest error, 4. Create Strategies and solutions to improve operational performance YOR and BOR PT Terminal Teluk Lamong, 5. Analyze the feasibility of investment on the results of strategies and solutions YOR and BOR. Results show correlation. value of 0489 which means quite a significant effect. The results of the modeling shows positive values so that forecasting would always go up. The value in the year 2020 forecast shows the optimum standard yet on YOR of 54.57% and the BOR is not good because it exceeds the standards established by the Government of the value of 76.74%. The results of the Analytical Hierarchy Process, shows that the main priority of the plan is the addition of length quay. The addition is planned to be a viable investment for the company with the highest Payback Period criteria 5 years 8 months, the Net Present Value of Rp447.341.169, Internal Rate of Return of 19% and Profitability Index of 1.91.